2014
DOI: 10.1111/poms.12064
|View full text |Cite
|
Sign up to set email alerts
|

Distributional and Peer‐Induced Fairness in Supply Chain Contract Design

Abstract: Members of a supply chain often make profit comparisons. A retailer exhibits peer-induced fairness concerns when his own profit is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(81 citation statements)
references
References 30 publications
2
78
1
Order By: Relevance
“…In fact, experimental studies examining triadic settings have reported considerable evidence of horizontal fairness concerns induced between peers (e.g., Gantner, Güth, & Königstein, 2001; Güth, Königstein, Kovtrueács, & Zala‐Meztrueõ, 2001; Königstein, Kovtrueács, & Zala‐Meztrueõ, 2003; Ho & Su, ; Ho, Su, & Wu, ). Additionally, they reveal that peer‐induced fairness in horizontal dimensions appears more salient than distributional fairness in the vertical dimension in determining subjects' behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, experimental studies examining triadic settings have reported considerable evidence of horizontal fairness concerns induced between peers (e.g., Gantner, Güth, & Königstein, 2001; Güth, Königstein, Kovtrueács, & Zala‐Meztrueõ, 2001; Königstein, Kovtrueács, & Zala‐Meztrueõ, 2003; Ho & Su, ; Ho, Su, & Wu, ). Additionally, they reveal that peer‐induced fairness in horizontal dimensions appears more salient than distributional fairness in the vertical dimension in determining subjects' behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they reveal that peer-induced fairness in horizontal dimensions appears more salient than distributional fairness in the vertical dimension in determining subjects' behaviors. Nevertheless, to the best of our knowledge, Ho et al (2014) is the only existing study incorporating horizontal fairness into the context of supply chain management. They investigate, both theoretically and experimentally, the role of fairness in a supply chain contract design, where one supplier sequentially offers two retailers a respective linear wholesale price contract, and each retailer must choose his own retail price if he accepts the suppliers wholesale price offer.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the assumption of the supplier having complete information of retailer's preferences in earlier works, Katok et al (2014) experimentally show that a wholesale price contract can also coordinate under information asymmetry when the fairness concerns of supply chain partners are strong enough. Along with distributional fairness, Ho et al (2014) also consider peer-induced fairness in a single supplier-two fair retailer setting and found that peer-induced fairness is more salient than distributional fairness. Wu and Niederhoff (2014) analyzed the impact of fairness concerns on profit allocations and supply chain performance in the newsvendor setting with general randomdemand function.…”
Section: Fairnessmentioning
confidence: 99%
“…For instance, Ho et al [27] explored differences between distributional and peer-induced fairness in supply chain contract design. They showed that the retailer made a lower share of the total supply chain in the presence of peer-induced fairness, and the experiment suggested that peer-induced fairness was more salient.…”
Section: Literature Reviewmentioning
confidence: 99%